2022
DOI: 10.3390/molecules27217174
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing SGLT2 Inhibitors for Neurological Disorders: A Focus on the Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder with a substantially increasing incidence rate. It is characterized by repetitive behavior, learning difficulties, deficits in social communication, and interactions. Numerous medications, dietary supplements, and behavioral treatments have been recommended for the management of this condition, however, there is no cure yet. Recent studies have examined the therapeutic potential of the sodium-glucose cotransporter 2 (SGLT2) inhibitors in neurodeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 163 publications
0
6
0
Order By: Relevance
“…SGLT2 was originally targeted for its role in glucose resorption in the kidney in patients with T2DM. SGLT2 now is viewed as having a potentially important role in cardiac and renal function, dementia, autism spectrum disorders, and other conditions in non-diabetic patients, independent of serum glucose [ 62 , 63 , 64 , 65 ]. The data presented here and previously [ 66 , 67 ] indicate that SGLT2 inhibitors also have potentially important protective effects in acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2 was originally targeted for its role in glucose resorption in the kidney in patients with T2DM. SGLT2 now is viewed as having a potentially important role in cardiac and renal function, dementia, autism spectrum disorders, and other conditions in non-diabetic patients, independent of serum glucose [ 62 , 63 , 64 , 65 ]. The data presented here and previously [ 66 , 67 ] indicate that SGLT2 inhibitors also have potentially important protective effects in acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in brain oxidative stress levels and AChE activity plays a crucial role in the pathogenesis of ASD-related behavioral features [ 34 , 35 , 36 ]. Several previous preclinical observations have shown that the SGLT2 inhibitor canagliflozin has displayed promising potential to mitigate oxidative stress and inflammation, in addition to its increasing effects on antioxidant capacity in numerous neurological disorders [ 15 , 16 , 17 , 22 , 27 ]. Therefore, the aim of the presented study was to evaluate the mitigating effects of canagliflozin on the oxidative stress levels in specific brain regions including the hippocampus, prefrontal cortex, and cerebellum of VPA-exposed rats with confirmed ASD-like behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, SGLT2 inhibitors have a variety of pleiotropic benefits, such as improving the visceral adiposity, reduction of body weight, lowering blood pressure, anti-inflammatory effect, oxidative stress downregulation, and normalizing serum uric acid levels as well as ameliorating lipid profile [ 14 ]. Interestingly, SGLT2 inhibitors such as canagliflozin and empagliflozin have shown promising results in the field of neurological disorders, including Alzheimer’s disease, Parkinson’s disease, and epilepsy [ 15 ], as they possess the advantage of crossing the blood–brain barrier (BBB), after which they have shown ability to reduce oxidative stress and inflammatory processes, which validates their activation, absorbance, and exposure profiles in the brain [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In addition, canagliflozin has been found to exhibit a dual activity on both SGLT1 and SGLT2 receptors, which are distributed in various brain areas of mammalian brain, such as the hippocampus, prefrontal cortex, and cerebellum [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 123 The expression of SGLT1 is greater than that of SGLT2. 124 SGLT2 inhibitors are dissolved in fat, pass through the blood-brain barrier via the transcytosis mechanism, 124 , 125 and modulate their receptors in the brain. 126 Based on the location of these receptors, the ability of SGLT2 inhibitors to pass, and their modulatory effects on their receptors, these drugs have neural effects.…”
Section: Nervous Systemmentioning
confidence: 99%
“… 130 The properties of Antioxidation, regulation of metabolic processes, and inhibition of the cholinesterase enzyme of SGLT2-inhibitor drugs may be used in the treatment of the autism spectrum of the disease. 124 It is still used in the treatment of Huntington’s disease based on its anti-apoptotic, anti-inflammatory, and anti-glycolytic properties. 131 …”
Section: Nervous Systemmentioning
confidence: 99%